2010
DOI: 10.4314/ijbcs.v4i3.60450
|View full text |Cite
|
Sign up to set email alerts
|

Faut-il éradiquer les Loranthaceae sur les ligneux à fruits commercialisés de la région littorale du Cameroun ?

Abstract: RESUMEDans la région du littoral camerounais, Phragmanthera capitata (généraliste) et Tapinanthus ogowensis (spécialiste) sont majoritaires dans la plupart des agroécosystèmes. Les deux Loranthaceae attaquent les essences cultivées ou spontanées d'importance économique ou non, réduisent les rendements et détériorent la qualité des fruits sous l'effet néfaste et conjugué de la salinité des sols. Les hémiparasites prélèvent sur leurs hôtes de l'eau et des substances minérales nécessaires à leur développement. Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 16 publications
0
1
0
3
Order By: Relevance
“…The using of mistletoes in the production of traditional soap and potash is justified by the high concentration of the leaves of these plants in potassium. Indeed, in Cameroon, Dibong et al [ 47 ] reported levels of up to 143.08 g of Potassium per kilogram of dry leaves of mistletoe. Given the high quantity of biomass it requires, intensifying the production of soap from mistletoe leaves will contribute to biological control these parasitic plants.…”
Section: Discussionmentioning
confidence: 99%
“…The using of mistletoes in the production of traditional soap and potash is justified by the high concentration of the leaves of these plants in potassium. Indeed, in Cameroon, Dibong et al [ 47 ] reported levels of up to 143.08 g of Potassium per kilogram of dry leaves of mistletoe. Given the high quantity of biomass it requires, intensifying the production of soap from mistletoe leaves will contribute to biological control these parasitic plants.…”
Section: Discussionmentioning
confidence: 99%
“…Most farmer and gardeners see mistletoes as notorious and devastating parasites which pose serious losses to economically-valuable fruit trees and medicinal plants gardens, orchards and wild forests. Host plants with high infestation suffer from poor growth, low productivity, quality harvest and death [10], with unfavourable edaphic and climatic conditions. Loranthaceae are widely distributed in tropical areas: America, Africa, and Australia; they extend to temperate regions with few representatives [11]; [12].…”
Section: Introductionmentioning
confidence: 99%
“…Elles sont présentes dans la plupart des groupements végétaux du Cameroun, y compris les mangroves. Elles sont perceptibles sur les cultures pérennes, les espèces fruitières dans les plantations, des jardins de cases et autres vergers, avec des taux et d'intensités d'infestation souvent très élevés (Dibong et al, 2010 ;Mony et al, 2014). Les espèces ligneuses d'importance environnementale et socio-économique telles que Terminalia sp., Dacryodes edulis, Psidium guajava, Citrus sp.…”
Section: Introductionunclassified
“…Au Cameroun, les plantes médicinales en général et les Loranthaceae en particulier, sont vendues régulièrement sur les marchés des centres urbains et ruraux en différentes saisons de l'année. Elles constituent des ressources précieuses pour de nombreuses populations des zones rurales en Afrique dont 80% de ces populations utilisent encore les plantes à caractère médicinal pour leur soin de santé primaire (Dibong et al, 2010 ;Adomou et al, 2012). Aujourd'hui, au-delà de leurs utilisations dans le traitement de différentes affections, l'exploitation durable des Loranthaceae est d'un grand intérêt pour les communautés locales à cause de ses retombées économiques par la commercialisation des bottes des espèces récoltées.…”
Section: Introductionunclassified